Study of the Effect of Changing the Speeds of the Potato Digging Machine on Work Quality - Botirovich, Akbarov Sherzod; Davlatjon qizi, Meliyeva Dildorakhon; Rakhmonali o‘g‘li, Mukhtarov Boburbek (American Journal of Biodiversity, 2025)
The study demonstrated a decrease in sieving efficiency due to uneven distribution of soil-tuber mass on the elevator surface in potato harvesting machines. To address this issue, a working element consisting of an elastic-fingered disk, installed perpendicular to the elevator plane, was employed. Field trial results showed that the proposed design increased soil screening efficiency by 12-17% compared to existing machines, maintained screening stability even at high speeds, and reduced tuber damage.